Entrepreneurship and emotions : insights on venture performance - Sassetti, Sara (Entrepreneurial behaviour series., 2021)
A key feature of being a successful entrepreneur is to have strong decision-making skills and decisions are best made when not swamped with emotion - either positive or negative. Investigating the emotional side of venture performance, Entrepreneurship and Emotions: Insights on Venture Performance presents hypotheses and tests theoretical frameworks exploring emotional intelligence effects and explains how these emotional components contribute to performance, both positive and negative. These impacts are analyzed, and the practical implications are presented, emphasizing the importance of considering and managing emotions during the entrepreneurial process. Grounded on a literature review and empirical evidences, Entrepreneurship and Emotions describes how emotions and the emotional intelligence of entrepreneurs has an impact on the venture performance. Readers will gain quantitative and reliable results about the relationship between affect, emotional intelligence, and venture performance.